The genomic organization and transcription of the ubiquitin genes of Trypanosoma cruzi. - Swindle, J (1988)
We describe here the organization of the ubiquitin genes of the parasitic protozoan Trypanosoma cruzi. T. cruzi contains greater than 100 ubiquitin coding sequences all of which are clustered into a 27 kb segment of the genome. Two types of ubiquitin coding sequences were found. There are five fusion genes (FUS1-5) consisting of a ubiquitin coding sequence fused to a basic non-ubiquitin sequence. The T. cruzi ubiquitin fusion protein is 84% homologous to the product of the UBI gene of Saccharomyces cerevisiae. The non-ubiquitin domains of the two proteins are 67% homologous. There are five polyubiquitin coding genes (PUB) each consisting of varying lengths of polyubiquitin coding sequence and terminating with a single copy of the larger fusion gene. Transcription of the ubiquitin genes results in the generation of six major poly(A)+ mRNAs. The pattern of transcription accurately reflects the genomic organization, in that the transcripts consist of either a single copy of the ubiquitin fusion coding sequence or varying lengths of polyubiquitin (up to 52 copies of the ubiquitin coding unit) each ending with a single copy of the ubiquitin fusion sequence. Finally, there are heat shock elements 5' to the PUB genes and transcription patterns are altered under conditions of stress.